PRESTASI KERJA KEGIATAN PENEBANGAN PT. BINA MULTI ALAM LESTARI DI KALIMANTAN TENGAH (Work Achievement Felling Activities PT. Bina Multi Alam Lestari in Central Kalimantan) : I Nyoman Surasana, Moh. Rizal, Jessika Simamora - JHT, Admin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2018)
ABSTRACTThe objectives of the research were to find out the composition of pure and generalworking time to total working time, work achievement of each felling team and averagework performance of all felling teams at the level of the sample size that was appropriatefor a research. The research method is Non Stop Method with t Test analysis. Fellingworkers observed were 3 (three) teams, samples were 35 trees/team or total sample were105 trees for 3 felling teams. The results showed that the average work time of the day:Team I = 191.33 minutes / day, Team II = 202.33 minutes / day, Team III = 190.00minutes / day, with average score (for the three squads ) = 194,55 minutes / day. Averageworking time composition (for all felling teams) in a day: Total Working Time (TWT) =194.55 minutes / day, Pure Work Time (PWT) = 179.02 minutes / day (92.01% of TWT )and General Working Time (GWT) = 15.53 minutes / day (7.99% of TWT). Averagefelling result: Team I = 50.03 m3 / day, Team II = 100.76 m3 / day, Team III = 63.25 m3/ day, with average score (for the three teams) = 72.01. Felling performance: Team I =16.32 m3 / hr, Team II = 29.88 m3 / hr, Team III = 19.97 m3 / hr, with average score (forthe three teams) = 22.06 m3 / hour. The result of t test shows the performance of TeamII is bigger than Team I and Team III, whereas Team I work achievement is notsignificantly different from Team III. The minimum number of samples required for thevalidity of this study was 61 units, while the number of samples that had been observedreached 105 units.Keywords: work result, felling, work achievement, working time.